Principles for modelling technological processes in transport terminal - Baublys, Adolfas (Transport, 2009)
A technological process is evaluated as a random process and assessed in respective models. The methodology of formalizing technological processes in the terminal and criteria for optimal control and the quality of the technological process are suggested. In addition, models and algorithms for the optimal control of freight clearing technological process are proposed.First published online: 27 Oct 2010